Perovskite photoelectric conversion devices based on inorganic hole conductors with high long-term operational stability
By introducing CuSCN and rGO spacers into organic-inorganic perovskite solar cells, the problems of perovskite layer deterioration and instability caused by inorganic hole conductors are solved, and efficient power conversion and long-term stability are achieved, exceeding the traditional HTM performance.
Patent Information
- Application Number
- CN201880039710.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-05-05
- Filing Date
- 2018-05-03
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2038-05-03
AI Technical Summary
The existing organic-inorganic perovskite solar cells have problems with perovskite layer deterioration and instability when using inorganic hole conductors, especially at high temperatures and long-term use, resulting in a decrease in power conversion efficiency.
The spacer layer, especially CuSCN and reduced graphene oxide (rGO), is introduced in the organic-inorganic perovskite solar cell, to isolate the inorganic hole conductor and back contact, prevent deterioration of the perovskite layer and improve stability.
By introducing the spacer layer, the long-term stability of the inorganic hole conductor solar cells is significantly improved, the initial efficiency of more than 90% is maintained, and the initial efficiency of 85% is maintained at high temperatures, exceeding the traditional spiral-OMeTAD benchmark.
Smart Images

Figure CN110754004B_ABST
Abstract
Description
Technical Field
[0001] The present invention generally relates to a photoelectric conversion device and an organic-inorganic perovskite-based photoelectric conversion device, in particular an organic-inorganic perovskite-based solar cell, wherein the photoelectric conversion device comprises an inorganic hole conductor and a spacer layer between the hole conductor layer and the back contact, which is highly stable over a long period of time and maintains an initial efficiency of more than 90% for a long period of time.
[0002] Prior art and the problem underlying the present invention
[0003] In the past two decades, the use of thin-film third-generation photovoltaics (PV) cells to convert solar energy into electric current has been widely explored. Sandwich / monolithic PV devices consisting of a mesoporous photoanode with an organic / inorganic light harvester, a redox electrolyte / solid hole conductor, and a counter electrode have gained significant attention due to ease of fabrication, flexibility in material selection, and cost effectiveness. In addition, tin-based organometallic halide perovskites (CsSnX 3 ) or lead-based organometallic halide perovskites (CH 3 NH 3 PbX 3 ; X=Cl, Br, I) have been introduced as light harvesters to replace traditional metal-organic complexes or organic molecules. Organic-inorganic hybrid lead halide or metal halide perovskite photovoltaic cells currently attract great research interest due to their low cost of manufacturing and materials and high solar-to-electrical power conversion efficiency (PCE). In the past five years, the PCE of perovskite solar cells (PSCs) has risen sharply from about 3% to 22.0%, which is unprecedented in the field of photovoltaic cells.
[0004] The prominence of organic-inorganic perovskite solar cells (PSCs) can be attributed to the unprecedented progress in power conversion efficiency (PCE), which is mainly achieved by tuning the formation and composition of the absorber layer.
[0005] A common organic-inorganic perovskite solar cell comprises a pair of electrodes and a perovskite active layer and a charge transport material arranged between them. The perovskite layer, with or without a mesoporous scaffold, is sandwiched between an electron transport layer and a hole transport layer (n-type and p-type, respectively). After photoexcitation, carriers are generated in the perovskite layer and negative and positive charge carriers are injected into the corresponding electron transport material and hole transport material, which are then collected as photocurrent at the front contact and back contact of the cell. There are two types of architectures: PSCs with conventional architectures or PSCs with inverted architectures. In PSCs with conventional architectures, the perovskite layer, with or without a mesoporous scaffold, is sandwiched between an electron layer on one side of a transparent front contact and a hole transport layer that contacts (indirectly or directly) the counter electrode. In a PSC with an inverted architecture, the perovskite layer is sandwiched between an electron blocking layer or hole collector layer and a hole blocking layer on one side of a transparent front contact, which may be in contact with a counter electrode or a metal electrode.
[0006] The fabrication of the hole transport layer is strictly controlled by the prepared active layer, which is usually sensitive to temperature, humidity and solvent. For these reasons, organic hole transport materials with excellent film processing properties become a better choice for this type of device. 2 Layer, and by using spiro-OMeTAD [2,2',7,7'-tetrakis(N,N-di-p-methoxyphenyl-amine)9,9'-spirobifluorene] or polymer-based PTTA (polytriarylamine) as hole transport materials (HTMs), recognized PCEs of more than 20% have been obtained. However, the cost of these HTMs is extremely high for large-scale applications, and long-term operational instability and thermal instability seem to be related to the prototype organic HTMs or their components. One of the strategies to overcome the problems of cost and instability may be to use an inexpensive inorganic hole extraction layer.
[0007] Therefore, inorganic HTMs such as NiO, CuI, CsSnI 3 and CuSCN are more favorable in terms of cost and durability. However, the use of inorganic HTMs in this type of device provides very poor performance. And it is still a challenge to obtain a stable PCE of more than 20% in the case of PSCs using inorganic HTMs when subjected to light soaking under practical operating conditions, i.e., at maximum power point and elevated temperature.
[0008] Different approaches have been taken to improve the performance of PSCs. One of these approaches involves different deposition methods using inorganic hole conductors, including doctor blading, electrodeposition, spin coating and spraying. Among them, the solution-based bottom-up approach is easier. However, a key problem associated with the solution-based approach is that most solvents in which the inorganic hole conductors show high solubility degrade the perovskite layer. In addition, because of the lack of solvents that easily dissolve inorganic hole conductors (such as CuSCN) instead of perovskites, inverted device architectures have been adopted, although with moderate success.
[0009] The present invention solves the high cost problem of using organic HTMs as hole transport materials (HTMs), such as, for example, spiro-OMeTAD [2,2',7,7'-tetrakis(N,N-di-p-methoxyphenyl-amine)9,9'-spirobifluorene] or polymer-based PTTA (polytriarylamine).
[0010] The present invention solves the problem of using an inorganic hole conductor or a p-type semiconductor in a PSC, degradation of the perovskite and instability of the device due to the use of such a hole conductor and the presence of a solvent that dissolves the perovskite.
[0011] The present invention solves the problem of long-term stability of PSCs with inorganic hole conductors, in particular the problem of thermal stability under long-term thermal stress.
[0012] The present invention solves the problems described above. SUMMARY OF THE INVENTION
[0014] The inventors surprisingly found that the introduction of a spacer layer, in particular CuSCN, in a PSC comprising an organic-inorganic perovskite and an inorganic hole conductor as HTM improves the performance of the PSC with the inorganic hole conductor. They comment that a spacer layer comprising reduced graphene oxide (rGO) between the metal contact or back contact of the device and the HTM layer comprising the inorganic hole conductor prevents a drastic loss of the PCE of such a PSC after treatment with continuous irradiation and thermal stress. The presence of such a spacer layer improves the long-term stability of the PSC comprising the inorganic hole conductor to such an extent that the stability of such a device exceeds the stability of the PSC based on spiro-OMeTAD.
[0015] In one aspect, the present invention provides an optoelectronic device and / or a photovoltaic device or a photoelectrochemical device, which includes a conductive support layer, an n-type semiconductor, a sensitizer layer or a light absorber layer, a hole transport layer, a spacer layer and a back contact, wherein the n-type semiconductor is in contact with the sensitizer layer or the light absorber layer, the sensitizer layer or the light absorber layer includes an organic-inorganic perovskite or a metal halide perovskite material, the hole transport layer is in direct contact with the sensitizer layer or the light absorber layer and includes an inorganic hole transport material or an inorganic p-type semiconductor, and the spacer layer is between the hole transport layer and the back contact and includes a material different from the inorganic hole transport material and the material of the back contact.
[0016] In another aspect, the present invention provides a method for manufacturing an optoelectronic device and / or a photovoltaic device or a photoelectrochemical device, the method comprising:
[0017] - providing a conductive support layer;
[0018] - disposing an n-type semiconductor on the conductive support layer;
[0019] - disposing a sensitizer layer or a light absorber layer comprising a perovskite or metal halide perovskite material on the n-type semiconductor;
[0020] - placing a hole transport layer on the sensitizer layer and subsequently applying a spacer layer;
[0021] - placing a counter electrode or a back contact electrode on the spacer layer;
[0022] wherein the hole transport layer comprises an inorganic hole transport material or an inorganic p-type semiconductor, and is deposited onto the sensitizer layer or the light absorber layer by a dynamic deposition method, the dynamic deposition method comprising depositing the inorganic hole transport material or the inorganic p-type semiconductor in a solution onto the sensitizer layer or the light absorber layer by a method selected from drop-casting, blade coating, electrodeposition, spin coating or spray coating while spinning a conductive support layer supporting the n-type semiconductor and the sensitizer layer or the light absorber layer; and
[0023] - the spacer layer comprises a material different from the inorganic hole transport material and the material of the back contact.
[0024] Further aspects and preferred embodiments of the invention are described in detail herein below and in the appended claims. From the description of preferred embodiments given below, further features and advantages of the invention will become apparent to those skilled in the art. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 A diagram showing a solid-state solar cell having a conventional architecture, from bottom to top, comprising Figure 1 a: Transparent conductive substrate (FTO), including a dense metal oxide layer (TiO 2 ) and mesoporous inorganic n-type semiconductor layer (TiO 2 ) as an n-type semiconductor, a perovskite layer, a hole transport layer (CuSCN) and a back contact (Au) of the scaffold structure of the perovskite material; Figure 1 b: with spacer layer Figure 1 The same frame as in a.
[0027] Figure 2 The structural characterization of a pristine, ie "pure," perovskite film not comprising any CuSCN layer as well as a CuSCN-coated perovskite film is shown. Figure 2 a: From pure CuSCN on glass, on perovskite / TiO 2 / CuSCN and bare perovskite on FTO / TiO 2 GIXD data obtained for TU / FTO. At the bottom, calculated powder diffraction data from CuSCN are shown for comparison. Indexing of the CuSCN pattern was performed according to the CuSCN 2H β-structure (black vertical lines correspond to the substrate). Figure 2 b: GIWAXS data from CuSCN, Figure 2 c: GIWAXS data from CuSCN+ perovskite. Figure 2 In c: The (002) reflection is clearly visible. The other reflections are superimposed with the stronger reflection from the perovskite film. Figure 2 d and Figure 2 e: Image depicts the preferred out-of-plane orientation (the in-plane orientation is rotated 90°); red balls represent copper atoms, yellow balls represent sulfur atoms, grey balls represent carbon atoms, and blue balls represent nitrogen atoms. Figure 2 f shows the intensity distribution of β-CuSCN: angular distribution of the intensity from the CuSCN (002) reflection on glass (black curve or top curve) and on perovskite (blue curve or bottom curve) after background subtraction (0° is parallel to the substrate plane; 90° is perpendicular).
[0028] Figure 3 Shown are the morphological characterization of pristine and CuSCN-coated perovskite samples, as well as steady-state and time-resolved photoluminescence studies performed on pristine and perovskite films containing different charge extraction layers. Figure 3 a, Deposition onto mesoporous TiO 2Top-view SEM micrograph of a perovskite film showing the presence of perovskite particles. Figure 3 b, Top view SEM micrograph showing the formation of a uniform CuSCN layer deposited onto the perovskite film. Figure 3 c, Cross-sectional SEM micrograph showing the thickness of the different layers throughout the device. Figure 3 d, Steady-state PL spectrum showing strong quenching of the intense PL exhibited by the pristine perovskite film. Figure 3 e, TCSPC showing persistent charge carriers in the pristine perovskite film and very fast charge injection from the perovskite film to the electron and hole extraction layers. ( Figure 3 d and Figure 4 The color code of e is the same). Figure 3 f and Figure 3 g shows the morphological characterization of spiro-OMeTAD-coated perovskite films and spiro-OMeTAD-based PSCs. Figure 3 f: Top view SEM micrograph of a spiro-OMeTAD layer deposited onto a perovskite film showing the presence of pinholes. Figure 3 g: Cross-sectional SEM micrograph showing the thickness of the different layers throughout the device.
[0029] Figure 4 Photovoltaic characterization of devices based on spiro-OMeTAD and CuSCN hole transport layers is shown. Figure 4 a, J-V curves of spiro-OMeTAD-based devices recorded at a scan rate of 0.01 V / s; the inset shows V as a function of illumination intensity. OC , where the ideality factor is 1.46. Figure 4 b, J-V curves of a CuSCN-based device recorded at a scan rate of 0.01 V / s; the inset shows the V as a function of the illumination intensity. OC , where the ideal factor is 1.51. Figure 4 c, JV metrology for 20 independent spiro-OMeTAD and CuSCN-based devices. Figure 4 d, Maximum power point (MPP) tracking for 60 s, yielding stabilized efficiencies of 20.5% and 20.3% for the spiro-OMeTAD-based device and the CuSCN-based device, respectively. Figure 4 e, EQE as a function of monochromatic wavelength recorded for spiro-OMeTAD-based and CuSCN-based devices and the integrated current density obtained from the corresponding EQE spectra. Figure 4f, Unencapsulated CuSCN-based device (PCE = 20.03%, see Figure 5 The operational stability of a 3D-printed perovskite device, comprising a thin layer of rGO as a spacer layer between the perovskite layer and the gold layer, was examined under continuous full-day illumination at 60 °C at maximum power point in a nitrogen atmosphere.
[0030] Figure 5 Shown are photovoltaic characterizations: JV characteristics of an optimized CuSCN device comprising a thin layer of rGO (reduced graphene oxide) as a spacer layer between the perovskite layer and the gold layer, recorded at a scan rate of 10 mV / s (reverse scan).
[0031] Figure 6 It shows that the use of Al 2 O 3 Operational stability of CuSCN-based devices (20 cycles). The photostability was examined at the maximum power point under continuous full-day illumination at 60 °C in a nitrogen atmosphere.
[0032] Figure 7 The operational stability of unencapsulated spiro-OMeTAD-based devices is shown. The photostability was examined at the maximum power point under continuous full-day illumination at 60 °C in a nitrogen atmosphere.
[0033] Figure 8 X-ray photoelectron spectroscopy is shown. Core-shell Au 4f spectra recorded from freshly deposited gold layers and gold layers removed from CuSCN based devices at 60°C for 50 h at maximum power point illumination.
[0034] Fig. 9 Stability test at 85° C. is shown. Thermal stability test of perovskite solar cells based on spiro-OMeTAD (sealed device, black curve or lower curve) and CuSCN (coated with a thin layer of PMMA, blue curve or top curve) aged at 85° C. in air in the dark for 1000 h. Error bars represent the standard deviation of a batch of four solar cells.
[0035] Fig.10 shows J as a function of the illumination intensity SC (Logarithmic scale). Fig.10 a: J in spiro-OMeTAD-based devices SC Light intensity dependence of (black solid squares), red solid line: linear fit. Fig.10 b: J in CuSCN-based device SC Light intensity dependence of (blue solid squares), red solid line: linear fit
[0036] Fig.11 Photovoltaic characterization is shown. Fig.11a: JV characteristics of the best device obtained after using concentrations of 15 mg / mL, 25 mg / mL and 45 mg / mL CuSCN in diethyl sulfide, recorded at a scan rate of 0.05 V / s (reverse scan). (Inset shows photovoltaic parameters extracted from the JV curves). Fig.11 b: JV curves of the best CuSCN-based device recorded at a scan rate of 0.05 V / s involving conventional deposition of CuSCN. (Inset shows photovoltaic parameters extracted from the JV curves).
[0037] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0038] The present invention provides an optoelectronic device and / or a photovoltaic device or a photoelectrochemical device, which comprises a conductive support layer, an n-type semiconductor, a sensitizer layer or a light absorber layer, a hole transport layer, a spacer layer and a back contact, wherein the n-type semiconductor is in contact with the sensitizer layer or the light absorber layer, the sensitizer layer or the light absorber layer comprises an organic-inorganic perovskite or metal halide perovskite material, the hole transport layer is in direct contact or in indirect contact with the sensitizer layer or the light absorber layer and comprises an inorganic hole transport material or an inorganic p-type semiconductor, the spacer layer is between the hole transport layer and the back contact or between the sensitizer layer or the light absorber layer and the hole transport layer and comprises a material different from the material of the inorganic hole transport material and the back contact, such as Figure 1 as shown in .
[0039] The optoelectronic device and / or photovoltaic device or photoelectrochemical device of the present invention is selected from photovoltaic devices, preferably solid-state solar cells. The photovoltaic device is selected from organic solar cells, solid-state solar cells, pn heterojunctions, phototransistors or OLEDs (organic light emitting diodes), preferably selected from solar cells or solid-state solar cells.
[0040] The spacer layer comprises a material, either conductive or non-conductive, which preferably prevents a reaction between the hole transport material or hole conductor and the back contact under stress, such as thermal stress, or under irradiation. If the spacer layer is present between the light absorber layer and the hole transport layer, it may also prevent a reaction between these two layers.
[0041] In one embodiment, the spacer layer comprises a material selected from the group consisting of reduced graphene oxide (rGO), graphene oxide, graphene, Ni, Co, Cr, Al 2 O 3 , Cu, C (carbon), ZrO 2 、SiO 2 、SiC、Si 3 N 4 , Ca 3 (PO 4 )2 , an insulating polymer selected from PMMA (polymethyl methacrylate), a polycarbonate polymer, and boron nitride (BN). Preferably, the spacer layer comprises a material selected from reduced graphene oxide, Cr and Al 2 O 3 materials.
[0042] In one embodiment, it is not excluded that the spacer layer may include a metal oxide material selected from the group consisting of Mg oxide, Hf oxide, Ga oxide, In oxide, Nb oxide, Ti oxide, Ta oxide, Y oxide and Zr oxide.
[0043] The thickness of the spacer layer depends on the electrical properties, but is typically from less than 1 nm to 5 nm, for example in the case of insulating materials, or from 10 nm to 20 nm, for example in the case of conductive or semiconductive layers. The thickness of the spacer layer is in the range of from less than 1 nm to 20 nm, from 5 nm to 15 nm, from 8 nm to 10 nm, from 2 nm to 5 nm. The spacer layer is preferably between the hole transport layer and the back contact.
[0044] In another embodiment, the n-type semiconductor includes a metal oxide layer. In particular, the n-type semiconductor includes a metal oxide layer that is a dense layer, on which a mesoporous metal oxide layer is disposed, the mesoporous metal oxide layer being a surface-increasing scaffold structure of an organic-inorganic perovskite or metal halide perovskite material. The n-type semiconductor includes a metal oxide layer selected from Si, TiO 2 SnO 2 、ZnO、Zn 2 SnO 4 , Nb 2 O 5 , WO 3 、BaTiO 3 or SrTiO 3 Or any combination thereof.
[0045] The n-type semiconductor as the electron transport layer is an inorganic material. The n-type semiconductor may be mesoporous and made of semiconductor particles. Preferably, the semiconductor particles are selected from TiO 2 and ZnO, most preferably TiO 2 The thickness of the n-type semiconductor layer is in the range from 50 nm to 1000 nm, preferably from 50 nm to 600 nm.
[0046] "Hole transport material", "hole transporting material", "organic hole transport material" and "inorganic hole transport material" and the like mean any material or composition in which charge is transported across the material or composition by the movement of electrons or holes (electronic motion). "Hole transport materials" are thus conductive materials. Such hole transport materials and the like are distinguished from electrolytes. In the latter, charge is transported by diffusion of molecules.
[0047] In another embodiment, the hole transport layer comprises one or more inorganic hole transport materials or inorganic p-type semiconductors selected from NiO, CuO, CuSCN, CuI, CuGaO 2 、CuCrO 2 、CuAlO 2 、CsSnI 3 、MoO 3 or WO 3 Or any combination thereof. Preferably, the semiconductor particles are selected from NiO, CuO, CuSCN, CuI. The thickness of the p-type semiconductor layer is in the range of from 40nm to 1000nm, from 40nm to 200nm, from 40nm to 70nm, from 40nm to 60nm. Preferably, the hole transport layer comprises a film without pinholes and having a thickness of from 40nm to 70nm. The hole transport layer is in the form of a uniform thin film without pinholes, i.e., a conformal structure or monotypism (only one type of layer stacking sequence) containing one type of hole transport material. Such a type of film is provided by a dynamic deposition method of a hole transport material in solution on a perovskite or sensitizer layer or light absorber layer, or if present, on a spacer layer, the method comprising a drop-casting step of spinning a hole transport material in solution, i.e. dissolved in a solvent selected from diethyl sulfide, propyl sulfide, or a mixture of diethyl sulfide and propyl sulfide, and drop-casting in a short period of time (2-3 seconds) while spinning at 5000 rpm. The hole transport layer is preferably free of p-dopants or other organic hole transport materials.
[0048] The deposition of inorganic p-type semiconductors is not limited to dynamic deposition. It can also include different methods such as blade coating, electrodeposition, spin coating and spray coating. The deposition of inorganic hole transport materials by this dynamic method, i.e. drop casting with rotation, allows to obtain very thin films without pinholes, which provides stability to the device against thermal stress and aging, and leads to the maintenance of about 85% of the initial PCE of the device during said thermal stress and aging treatment.
[0049] According to another embodiment, the conductive support layer includes a conductive material selected from the group consisting of an indium tin oxide (ITO) film substrate, a fluorine-doped tin oxide (FTO) film substrate, a ZnO-Ga 2 O 3 Film substrate, ZnO-Al 2 O 3 Film substrates, tin-based oxide film substrates, antimony-doped tin oxide (ATO), SrGeO 3 or zinc oxide. Preferably, the conductive support layer comprises a transparent substrate covered by a conductive material. Specific examples of the transparent substrate include, but are not limited to, a glass substrate, a transparent inorganic substrate, such as quartz and glass; a transparent plastic substrate, such as poly(ethylene terephthalate) (PET), poly(ethylene 2,6-naphthalate) (PEN), polycarbonate (PC), polyethylene (PE), polypropylene (PP) and polyimide (PI). Preferably, the material of the transparent substrate is glass.
[0050] The electrically conductive support layer preferably functions as and / or comprises a current collector, which collects the electrical current obtained from the solar cell.
[0051] The back contact generally comprises a catalytically active material suitable for providing electrons and / or filling holes toward the inner side of the device. The back contact may comprise one or more materials selected from the following: Pt, Au, Ni, Cu, Ag, In, Ru, Pd, Rh, Ir, Os, porous carbon (C), a conductive polymer, and a combination of two or more of the above. The conductive polymer may be selected from a polymer including polyaniline, polypyrrole, polythiophene, polybenzene, polyethylene dioxythiophene, polypropylene dioxythiophene, polyacetylene, and a combination of two or more of the above, for example.
[0052] In an embodiment, the back contact comprises a material selected from a metal, porous carbon or a conductive polymer as defined above or a combination thereof, the metal being selected from Pt, Au, Ni, Cu, Ag, In, Ru, Pd, Rh, Ir, or Os. Preferably, the back contact is selected from gold (Au), silver (Ag), aluminum (Al), copper (Cu), platinum (Pt), nickel (Ni). In addition, the back contact is more preferably gold (Au) having a thickness between 50 nm and 200 nm. In addition, the electrode may be porous carbon (C).
[0053] For the purposes of this specification, the term “perovskite” refers to the “perovskite structure” and does not refer exclusively to the perovskite material CaTiO 3For the purposes of this specification, "perovskite" includes and preferably refers to any material having a crystal structure of the same type as calcium titanium oxide and a material in which the divalent cation is replaced by two separate monovalent cations. The perovskite structure has a general stoichiometry of AMX 3 , where "A" and "M" are cations and "X" is an anion. The "A" and "M" cations can have a variety of charges and are present in the original perovskite mineral (CaTiO 3 ), the A cation is divalent and the M cation is tetravalent. For the purposes of the present invention, the perovskite formula includes structures having three or four anions (the three or four anions may be the same or different), and / or one or two organic cations, and / or metal atoms carrying two or three positive charges, according to the chemical formulas presented elsewhere in this specification.
[0054] The sensitizer layer or light absorber layer may include one or more layers of an organic-inorganic perovskite or a metal halide perovskite. In the device, the last upper layer of the organic-inorganic perovskite or metal halide perovskite is coated with a hole transport material or, if present, a spacer layer. The organic-inorganic perovskite or metal halide perovskite may be disposed on a mesoscopic part of an n-type semiconductor on a metal oxide layer.
[0055] According to another embodiment, the perovskite or metal halide perovskite is selected from the perovskite structure according to any one of the following formula (I), formula (la), formula (lb), formula (Ic), formula (Id), formula (le), formula (If) and / or formula (Ig):
[0056] AA'MX 4 (I)
[0057] AMX 3 (Ia)
[0058] AA'N 2 / 3 X 4 (Ib)
[0059] AN 2 / 3 X 3 (Ic)
[0060] BN 2 / 3 X 4 (Id)
[0061] BMX 4 (Ie)
[0062] (A l )m AA'MX 3 (If)
[0063] (A l ) m AMX 3 (Ig)
[0064] in,
[0065] - A and A' are organic monovalent cations, the organic monovalent cations are independently selected from organic primary ammonium compounds, organic secondary ammonium compounds, organic tertiary ammonium compounds or organic quaternary ammonium compounds, including N-containing heterocyclic rings and ring systems, A and A' independently have from 1 to 60 carbons and 1 to 20 heteroatoms;
[0066] -A l Is selected from Cs + , Rb + , K + An inorganic cation, and m is an integer from 1 to 3, if m>1, then each A l different;
[0067] - B is an organic divalent cation selected from an organic primary ammonium compound, an organic secondary ammonium compound, an organic tertiary ammonium compound or an organic quaternary ammonium compound having from 1 to 60 carbon atoms and 2-20 heteroatoms and having two positively charged nitrogen atoms;
[0068] -M is selected from Cu 2+ 、Ni 2+ 、Co 2+ , Fe 2+ , Mn 2+ Cr 2+ , Pd 2+ 、Cd 2+ ,Ge 2+ Sn 2+ , Pb 2+ 、Eu 2+ , Yb 2+ 、[Sn i Pb (1-i) ] + 、[Sn j Ge (1-j) ] + and [Pb k Ge (1-k) ] + , i, j, and k are numbers between 0.0 and 1.0;
[0069] -N is selected from Bi 3+ and Sb 3+ groups; and,
[0070] -X is independently selected from Cl - Br - ,I - 、NCS - , CN - 、NCO - ; [I (3-m) Cl m ] - , [I (3-n) Br n ] - , [Br (3-u) Cl u ] - , m, n, u are numbers between 0.0 and 3.0; and selected from C1 - Br - ,I - A combination of two anions.
[0071] In particular, the three or four Xs may be the same or different. For example, in AMX 3 (Formula Ia) can be represented by the following formula (Ia'):
[0072] AMXiXiiXiii(Ia')
[0073] Wherein Xi, Xii, Xiiii are independently selected from Cl - Br - ,I - 、NCS - , CN - 、NCO - ; [I (3-m) Cl m ] - , [I (3-n) Br n ] - , [Br (3-u) Cl u ] - , m, n, u are numbers between 0.0 and 3.0; and selected from C1 - Br - ,I - The combination of two anions is preferably selected from halides (C1 - Br - ,I - ), and A and M are as defined elsewhere in this specification. Xi, Xii, Xiii can therefore be identical or different in this case.
[0074] Preferably, if Xi, Xii, Xiiii in formula (Ia) and formula (Ic) or Xi, Xii, Xiiii, Xiv in formula (I), formula (Ib), formula (Id) or formula (Ie) contain different anions X, then there are no more than two different anions. For example, Xi and Xii are the same, wherein Xiiii is an anion different from Xi and Xii.
[0075] According to the perovskite structure of formula (If) or formula (Ig), A and A′ are independently selected from methylammonium cation, formamidinium cation, iodo-carbamimidoyl cation or a combination of said cations.
[0076] According to a preferred embodiment, the perovskite or metal halide perovskite layer comprises a perovskite structure according to any one of formula (Ih) to formula (Im):
[0077] APx 3 (Ih)
[0078] AHr 3 (Ii)
[0079] ABiX 4 (Ij)
[0080] AA'PbX 4 (Ik)
[0081] AA'SnX 4 (IIj)
[0082] BX 4 (Il)
[0083] SXWh 4 (Im)
[0084] wherein A, A', B and X are as defined above in this specification. Preferably, X is preferably selected from Cl - Br - and I - , most preferably X is I - , or Br - and I - mixture.
[0085] The sensitizer layer or light absorber layer comprising an organic-inorganic perovskite or a metal halide perovskite may comprise a perovskite structure according to any one of Formula (If) to Formula (Im), more preferably Formula (If), Formula (Ih) and / or Formula (Ii).
[0086] According to an embodiment, A and A' are monovalent cations independently selected from any one of the following compounds of formula (20) to formula (28):
[0087]
[0088] in,
[0089] R 7 , R 8 , R 9 and R 10 Independently selected from C1-C15 organic substituents containing from 0 to 15 heteroatoms.
[0090] According to the embodiment of the C1-C15 organic substituent, any one, several or all hydrogens in the substituent may be replaced by halogen, and the organic substituent may contain up to fifteen (15) N, S or O heteroatoms, and wherein, in any one of compounds (20) to (28), the substituent (R 7 , R 8 , R 9 and R 10 , if applicable) can be covalently linked to each other to form a substituted or unsubstituted ring or ring system. Preferably, in the chain of atoms of the C1-C15 organic substituent, any heteroatom is connected to at least one carbon atom. Preferably, in the C1-C15 organic substituent comprising from 0 to 15 heteroatoms, adjacent heteroatoms do not exist and / or heteroatom-heteroatom bonds do not exist. The heteroatom can be selected from N, S and / or O.
[0091] According to the embodiment, R 7 , R 8 , R 9 and R 10 independently selected from C1 to C15 aliphatic substituents and C4 to C15 aromatic substituents or heteroaromatic substituents, wherein any one hydrogen, several hydrogens or all hydrogens in said substituents may be replaced by halogen and wherein, in any of compounds (20) to (28), two or more of the substituents present may be covalently linked to each other to form a substituted or unsubstituted ring or ring system.
[0092] According to a preferred embodiment, the organic-inorganic perovskite is selected from compounds of formula (I), formula (Ia), formula (If) or formula (Ig).
[0093] According to an embodiment, B is a divalent cation selected from any one of the following compounds of formula (49) and formula (50):
[0094]
[0095] in,
[0096] In the compound of formula (29), G is an organic linker structure having 1 to 10 carbon atoms and 0 to 5 heteroatoms selected from N, S and / or O, wherein one or more hydrogen atoms in G may be replaced by halogen;
[0097] Where R 11 and R 12 A compound independently selected from any one of formula (20) to formula (28); and wherein, in the compound of formula (30), the circle containing the two positively charged nitrogen atoms represents a substituted or unsubstituted aromatic ring or ring system, the ring or ring system containing 4 to 15 carbon atoms and 2 to 7 heteroatoms or 4 to 10 carbon atoms and 2 to 5 heteroatoms, wherein the nitrogen atom is a ring heteroatom of the ring or ring system, and wherein the remaining heteroatoms of the heteroatoms can be independently selected from N, O and S and wherein R 13 and R 14 Independently selected from H and any one of formulae (20) to (28). In addition to and / or independently of the 2 to 7 heteroatoms, halogen atoms may be present which fully or partially replace the hydrogen atoms.
[0098] Preferably, if the number of carbons in G is an odd number, the number of heteroatoms is less than the number of carbons. Preferably, in the ring structure of formula (30), the number of ring heteroatoms is less than the number of carbon atoms. According to an embodiment, G is an aliphatic, aromatic or heteroaromatic linker structure having from 1 to 10 carbons.
[0099] According to the embodiment, R 7 , R 8 , R 9 and R 10 independently selected from C1 to C10 alkyl, C2 to C10 alkenyl, C2 to C10 alkynyl, C4 to C10 heteroaryl and C6 to C10 aryl, wherein if the alkyl, alkenyl, and alkynyl contain 3 or more carbons, they can be linear, branched or cyclic, wherein the heteroaryl and aryl can be substituted or unsubstituted, and wherein in R 7 , R 8 , R 9 and R 10 Some or all of the hydrogens in may be replaced by halogens.
[0100] According to the embodiment, R 7 , R 8 , R 9 and R 10independently selected from C1 to C8 alkyl, C2 to C8 alkenyl, C2 to C8 alkynyl, C4 to C8 heteroaryl and C6 to C8 aryl, wherein if the alkyl, alkenyl, and alkynyl contain 3 or more carbons, they can be linear, branched or cyclic, wherein the heteroaryl and aryl can be substituted or unsubstituted, and wherein in R 7 , R 8 , R 9 and R 10 Some or all of the hydrogens in may be replaced by halogens.
[0101] According to the embodiment, R 7 , R 8 , R 9 and R 10 independently selected from C1 to C6 alkyl, C2 to C6 alkenyl, C2 to C6 alkynyl, C4 to C6 heteroaryl and C6 aryl, wherein if the alkyl, alkenyl, and alkynyl contain 3 or more carbons, they can be linear, branched or cyclic, wherein the heteroaryl and aryl can be substituted or unsubstituted, and wherein in R 7 , R 8 , R 9 and R 10 Some or all of the hydrogens in may be replaced by halogens.
[0102] According to the embodiment, R 7 , R 8 , R 9 and R 10 independently selected from C1 to C4 alkyl, C2 to C4 alkenyl and C2 to C4 alkynyl, wherein if the alkyl, alkenyl, and alkynyl groups contain 3 or more carbons, they may be linear, branched or cyclic, and wherein in R 7 , R 8 , R 9 and R 10 Some or all of the hydrogens in may be replaced by halogens.
[0103] According to the embodiment, R 7 , R 8 , R 9 and R 10 independently selected from C1 to C3 alkyl, preferably C1 to C2 alkyl, C2 to C3 alkenyl, preferably C2 alkenyl and C2 to C3 alkynyl, preferably C2 alkynyl, wherein if the alkyl, alkenyl, and alkynyl contain 3 or more carbons, they may be linear, branched or cyclic, and wherein in R 7 , R 8 , R 9 and R 10 Some or all of the hydrogens in may be replaced by halogens.
[0104] According to the embodiment, R 7 , R 8 , R 9 and R 10 are independently selected from C1 to C4 alkyl, more preferably C1 to C3 alkyl and even more preferably C1 to C2 alkyl. Most preferably, R 7 , R 8 , R 9 and R 10 is a methyl group. Again, the alkyl group may be fully or partially halogenated.
[0105] According to an embodiment, A, A' and B are respectively monovalent (A, A') cations and divalent (B) cations selected from substituted and unsubstituted C5 to C6 rings containing one, two or more nitrogen heteroatoms, wherein one (for A and A') or both (for B) of the nitrogen atoms are positively charged. The substituents of such rings may be selected from halogen and selected from C1 to C4 alkyl, C2 to C4 alkenyl and C2 to C4 alkynyl as defined above, preferably selected from C1 to C3 alkyl, C3 alkenyl and C3 alkynyl as defined above. The ring may contain additional heteroatoms, which may be selected from O, N and S. The divalent organic cation B comprising two positively charged ring N atoms is exemplified, for example, by compounds of formula (30) above. Such rings may be aromatic or aliphatic.
[0106] A, A' and B may also include a ring system comprising two or more rings, at least one of which is from a substituted and unsubstituted C5 to C6 ring as defined above. The oval circles in the compounds of formula (30) may also represent a ring system comprising, for example, two or more rings, but preferably two rings. In addition, if A and / or A' comprises two rings, additional ring heteroatoms may be present, for example, the additional ring heteroatoms are preferably uncharged.
[0107] However, according to an embodiment, the organic cations A, A' and B contain one (for A, A'), two (for B) or more nitrogen atoms, but do not contain any O or S or any other heteroatom, except halogen, which can replace one or more hydrogen atoms in cations A and / or B.
[0108] A and A' preferably contain one positively charged nitrogen atom. B preferably contains two positively charged nitrogen atoms.
[0109] A, A' and B may be selected from the following exemplary rings or ring systems of formula (31) and formula (32) (for A, A') and from formula (33) to formula (35) (for B):
[0110]
[0111] in
[0112] R 7 and R 8 is selected from the substituents defined above, and R 14 , R 15 , R 16 , R 17 , R 18 , R 19 , R 20 and R 21 independently selected from H, halogen and as described above for R 7 , R 8 , R 9 and R 10 Preferably, R 14 , R 15 , R 16 , R 17 , R 18 , R 19 , R 20 and R 21 is selected from H and halogen, most preferably H.
[0113] In the organic cations A, A' and B, hydrogen atoms may be substituted by halogens such as F, Cl, I and Br, preferably F or Cl. Such substitutions are expected to reduce the hygroscopicity of one or more perovskite layers and thus may provide a useful option for the purposes of this specification.
[0114] According to a preferred embodiment, A and A' are independently selected from organic cations of formula (20) and / or formula (28).
[0115] According to a preferred embodiment, the metal M is selected from Sn 2+ and Pb 2+ , preferably Pb 2+ According to a preferred embodiment, N is Sb 3+ .
[0116] According to a preferred embodiment, three or four X are independently selected from Cl - Br - and I - .
[0117] In a further aspect, the present invention provides a method for making a solid-state solar cell or optoelectronic device and / or photovoltaic device or photoelectrochemical device, the method comprising:
[0118] - providing a conductive support layer;
[0119] - disposing an n-type semiconductor on a conductive support layer;
[0120] - placing a sensitizer layer or a light absorber layer on the n-type semiconductor;
[0121] - placing a hole transport layer on the sensitizer layer or light absorber layer and subsequently applying a spacer layer; or
[0122] - placing a spacer layer on the sensitizer layer or light absorber layer and subsequently applying a hole transport layer;
[0123] - Arrange the counter electrode or the back contact electrode on the hole transport layer or on the spacer layer.
[0124] According to one embodiment, the hole transport layer provided comprises an inorganic hole transport material or an inorganic p-type semiconductor as defined above and is deposited onto the sensitizer layer or light absorber layer by a dynamic deposition method comprising depositing the inorganic hole transport material or inorganic p-type semiconductor in solution onto the sensitizer layer or light absorber layer by a method selected from drop casting, blade coating, electrodeposition, spin coating or spray coating while rotating a conductive support layer supporting an n-type semiconductor and a sensitizer layer or light absorber layer. Preferably, the application of the inorganic hole transport material is provided by spin coating while rotating a conductive support supporting a layer below the hole transport layer.
[0125] According to an embodiment, the step of providing a hole transport layer comprises applying a hole transport material by drop casting said hole transport material in a solution onto a sensitizer layer or a light absorber layer or, if present, a spacer layer, and a step of rotating. The step of rotating is carried out at a rotation speed of from 4000 rpm to 6000 rpm, from 4500 rpm to 5500 rpm, preferably 5000 rpm, or from 66.67 Hz to 100 Hz, 75 Hz to 91.67 Hz, preferably 83.34 Hz. The hole transport material is an inorganic hole transport material as defined above.
[0126] The present invention is more specifically described with reference to the following examples, however, the following examples are not intended to limit the scope of the present invention. Example
[0127] Example 1: Preparation of organic-inorganic perovskite-based devices
[0128] TiO 2 Preparation of the photoanode.
[0129] Fluorine-doped tin oxide (FTO)-glass substrates (TCO glass, NSG 10, Nippon sheet glass, Japan) were cleaned by ultrasonic treatment in Hellmanex (2%, deionized water) for 30 min, thoroughly rinsed with deionized water and ethanol, and then treated in oxygen plasma for 15 min. About 30 nm of TiO was subsequently deposited via spray pyrolysis at 450 °C from a precursor solution of commercial titanium diisopropoxide bis(acetylacetonate) (75% in 2-propanol, Sigma-Aldrich) diluted in anhydrous ethanol (1:9, volume ratio) and oxygen as carrier gas. 2 Then the mesoporous TiO 2 The layer was rotated at a speed of 4000 rpm and accelerated to 2000 rpm for 20 s (TiO 2 The weight ratio of Dyesol paste (30 NRD) and ethanol is 1:6) and the diluted paste is spin-coated onto the TiO 2 This is followed by sintering the substrate at 450 °C for 30 min in a dry gas stream. 2 Li treatment of the scaffold, after a loading time of 10 s, spin coating (3000 rpm, acceleration 2000 rpm, for 20 s) 150 μL of LiTFSI (bis(trifluoromethylsulfonyl)imide lithium salt) solution in acetonitrile (10 mg / mL, freshly prepared in an argon atmosphere) was performed. Thereafter, the Li-treated substrate was subjected to a second sintering step at 450 ° C in dry air for 30 min. After cooling to 200 ° C, the substrate was transferred to a dry air glove box (humidity <1%) for perovskite deposition.
[0130] Preparation of perovskite.
[0131] The perovskite film was deposited using a one-step deposition method from a mixture of FAI (1.0 M) (Dyesol), PbI 2 (1.1M)(TCI), MABr(0.2M)(Dyesol) and PbBr 2 The precursor solution was spin-coated onto the mesoporous TiO2 at 1000 rpm and 6000 rpm in a two-step procedure.2 The film was then annealed for 10 s and 30 s. During the second step, 100 μl of chlorobenzene (99.8%, Acros) was dropped on the rotating substrate 10 s before the end of the program. This was followed by annealing the film at 100°C for 45 min. Perovskite deposition was performed in a dry air glove box under controlled atmospheric conditions with humidity <1%.
[0132] Deposition of hole transport layer.
[0133] To complete the device fabrication, 2,2',7,7'-tetrakis(N,N-di-p-methoxyanilino)-9,9-spirobifluorene (spiro-OMeTAD, 70 mM in chlorobenzene) as a hole transport material (HTM) was deposited by spin coating 40 μL of the prepared solution at 4000 rpm for 30 s. Spiro-OMeTAD (Merck) was doped with bis(trifluoromethylsulfonyl)imide lithium salt, tris(2-(1H-pyrazol-1-yl)-4-tert-butylpyridinium)-cobalt(III)tris(bis(trifluoromethylsulfonyl)imide) (FK 209 from Dyenamo) and 4-tert-butylpyridine (96%, Sigma-Aldrich) at molar ratios of 0.5, 0.03 and 3.3, respectively. CuSCN solution was prepared by dissolving CuSCN salt (99%, Sigma-Aldrich) in 1mL of diethyl sulfide (98%, Sigma-Aldrich) after continuous stirring at room temperature for 30min. In order to deposit a thin and uniform CuSCN film, 35μL of CuSCN solution was drop-cast on a substrate containing a perovskite film rotating at 5000rpm in 2-3 seconds, and the substrate was allowed to rotate for 30 seconds. As in the case of spiro-OMeTAD deposition, no post-heat treatment was applied. The deposition of the hole transport layer was carried out in a dry air glove box with humidity <1%. Finally, the device fabrication was completed by thermal evaporation of a 60nm gold layer as the back contact.
[0134] Al 2 O 3 Deposition of spacer layer.
[0135] A Savannah ALD system from Cambridge Nanotech, USA, was used to generate trimethylaluminum (Al(CH 3 ) 3 ) (Sigma Aldrich) and deionized H 2 Al deposition in O 2 O 3 . Use N 2(99.999%) was used as an inert carrier gas to pulse the precursor into the reactor. Water was pulsed for 0.015 s and confined in the reactor for 60 s, followed by a purge of TMA for 0.015 s and waiting for another 60 s. 20 ALD cycles were applied to achieve a thickness of ~2 nm.
[0136] Deposition of rGO spacer layer.
[0137] A thin layer (~10 nm thickness) of reduced graphene oxide (Ossila) was deposited by spin coating a solution (filtered) containing reduced graphene oxide (1 mg / mL in chlorobenzene, sonicated for 30 min) onto the CuSCN layer at 3000 rpm.
[0138] Example 2: Measurement of photovoltaic properties and stability of perovskite-based devices
[0139] Structural characterization.
[0140] X-ray scattering experiments were performed at the ID10 EH1 beamline of the ESRF with a photon energy of 22 keV under a nitrogen atmosphere. The beam size was 10 μm in the vertical direction and 120 μm in the horizontal direction. GIXD data were measured at an incident angle of 0.08° with a point detector. GIWAXS data were measured at the same incident angle with a PILATUS 300k area detector. Calculations of powder diffraction data were completed with mercury.
[0141] Morphological characterization.
[0142] Field emission scanning electron microscopy (Merlin) was used to examine the morphology of the perovskite film and the thickness of each layer. An electron beam accelerated to 3 kV was used with an in-lens detector. X-ray photoelectron spectroscopy.
[0143] X-ray photoelectron spectroscopy (XPS) was performed on an X-ray photoelectron spectrometer (ESCALAB 250Xi, Thermo Fisher SCIENTIFIC INC., USA) with Al Kα radiation (hυ=1486.6 eV) as the source.
[0144] Charge extraction by linearly increasing voltage
[0145] The fully assembled device was connected to a function generator and measurements were taken with an oscilloscope across a small load resistor to minimize RC effects of the circuit.The mobility was measured across a range of electric fields, determined by the field where the maximum current was extracted.
[0146] Photoluminescence research
[0147] Photoluminescence and time-resolved photoluminescence spectra were recorded on a spectrofluorimeter Fluorolog 322. Photoluminescence spectra were recorded by exciting the samples with a 450 W xenon lamp at a fixed wavelength of 450 nm and scanning the emission monochromator from 625 nm to 850 nm. The same spectrometer operated in time-correlated single photon counting mode was used to measure the photoluminescence decay kinetics with sub-nanosecond time resolution. A diode laser head NanoLED-405LH (Horiba) emitting picosecond pulses of <200 ps duration at 408 nm at a repetition rate of 1 MHz was used as the excitation source. For electron injection studies, the samples were removed from TiO 2 The side is excited, while for studying the photoluminescence decay dynamics of pristine and HTM-containing samples, the samples are excited from the top.
[0148] Photovoltaic Research
[0149] The current-voltage (JV) characteristics of the perovskite device were recorded with a digital source meter (Keithley 2400 model, USA). A 450W xenon lamp (Oriel, USA) was used as the light source for photovoltaic (JV) measurements. The light source was equipped with a Schott K113 Tempax sunlight filter (Praezisions Glas and Optik GmbH) to make the emission spectrum of the lamp conform to the AM1.5G standard. Before each measurement, a calibrated Si reference diode equipped with an infrared cutoff filter (infrared cutoff filter) (KG-3, Schott) was used to determine the exact light intensity. A dark metal mask was used to define a 0.16 cm 2 The external quantum efficiency (EQE) was measured using an LED light source (Ariadne EQE from Cicci Research).
[0150] Stability test
[0151] Light stability tests were performed at maximum power point at 60°C under one-sun illumination using a homemade electronic board with eight-channel maximum power point capability. The channels are equipped with DACs (DAC7563), level shifters (INA2132), and output line drivers (OPA2192). The drive lines have a 12-bit resolution (1mV per bit) in the range of ±2.048V. The buffer output is connected to the battery through a 0.5-ohm sense resistor. The voltage drop is amplified (INA188) to sense the current. The voltage is buffered (OPA2188) to sense the voltage. The signal line is multiplexed (CD54HC4051) into a fourth order active Butterworth filter with its pole set at 500Hz. Data conversion is performed by an analog-to-digital converter (ADS1118) at 430SPS. The DAC and ADC are interfaced through an Atmega328 microcontroller. The light source consisting of an array of white LEDs is powered by a constant current and does not use a filter (UV). The equivalent sunlight intensity is calibrated using a calibrated Si reference diode equipped with a KG-3 filter. The Keithley 2602B source measurement unit is used to calibrate the setup periodically. For thermal stability testing, a device based on CuSCN is coated with a thin layer (30 nm) of PMMA (20 mg / mL in chlorobenzene) on top of the gold layer. Thermal stability testing is carried out by aging devices at 85 ° C in an oven, and the photovoltaic efficiency is regularly recorded under AM1.5 simulated sunlight.
[0152] Hole transport layer: a thin film without pinholes provided by spin drop casting
[0153] Achieving >20% efficiency using PSCs with inorganic hole transport materials undoubtedly remains a key goal to promote the large-scale deployment of PSCs. Among the various inorganic hole transport materials, CuSCN is an extremely cheap, abundant p-type semiconductor that exhibits high hole mobility, good thermal stability, and well-aligned workfunction. CuSCN is inherently p-doped and transmits light across the entire visible and near-infrared spectral regions, so it is also attractive for tandem cell applications in which PSCs are placed on top of lower bandgap semiconductors. However, the stabilized PCE values reported with CuSCN lag far behind those of standard spiro-OMeTAD-based devices. Different methods have been tried for CuSCN deposition, including blade coating, electrodeposition, spin coating, and spray coating. Among these, solution-based bottom-up methods are easier to implement; however, the key problem associated with them is that most solvents in which CuSCN shows high solubility degrade the perovskite layer ( Fig.11 b) Primarily, because of the lack of solvents that readily dissolve CuSCN but not perovskites, inverted device architectures have been employed, albeit with moderate success.
[0154] In order to maintain the mesoscopic TiO 2 Here, we developed a simple dynamic deposition method to achieve a conventional device architecture. Typically, we deposited CuSCN in CsFAMAPbI by drop-casting a defined volume of CuSCN dissolved in diethyl sulfide over 2 to 3 s while rotating the substrate at 5000 rpm. 3-x Br x (MA=CH 3 NH 3 + FA=CH(NH 2 ) 2 + ) a thin and uniform CuSCN layer is deposited on top of the perovskite layer without compromising the quality of the perovskite layer ( Fig.11 a). The structural features of the resulting CuSCN layers were investigated using X-ray diffraction. CuSCN crystallizes as two polymorphs, α-CuSCN and β-CuSCN, the latter of which exhibits polytypism, i.e. variations in the stacking order of the layers. Comparison of the calculated powder XRD spectrum of CuSCN with grazing incidence X-ray diffraction (GIXD) data ( Figure 2 a) Demonstrates that the dynamic deposition method produces β-CuSCN. The broad reflections at 100 nm confirmed the presence of different polytypes of β-CuSCN, mainly 2H and 3R. The size of the coherently scattering islands of 17 nm and 18 nm were estimated using the peak width of the (002) reflection of CuSCN deposited on glass and perovskite films, respectively. In addition, to determine the domain orientation, we obtained grazing-incidence wide-angle X-ray scattering (GIWAXS) data from CuSCN and CuSCN / perovskite films ( Figure 2 b and Figure 2 c). Intensity distribution of the (002) β-CuSCN ring ( Figure 2 f), it is evident that the CuSCN domains have a preferred orientation with the long unit cell axis parallel to the substrate ( Figure 2 d and Figure 2 e).
[0155] Before the deposition of the CuSCN layer ( Figure 3 a) and after deposition of the CuSCN layer ( Figure 3b) Scanning electron microscope (SEM) micrograph of the obtained perovskite film shows that the perovskite capping layer is uniformly covered by the CuSCN layer. In contrast, for the spiro-OMeTAD layer deposited via conventional spin coating, the presence of pinholes is very obvious ( Figure 3 f), which could be detrimental to performance. To assess the thickness of each layer, we obtained cross-sectional SEM micrographs of the entire device ( Figure 3 c), which confirms the formation of a ~60 nm thin CuSCN layer sandwiched between the perovskite capping layer and the gold layer. We used steady-state photoluminescence (PL) and time-correlated single photon counting (TCSPC) spectroscopy to study the carrier dynamics in the pristine perovskite film and the perovskite film containing the HTM. The pristine perovskite film exhibits strong PL emission centered at about 773 nm with a linewidth of 44 nm ( Figure 3 d). In the presence of the charge extraction layer, the PL of the pristine perovskite film is strongly quenched, from which we can infer a very fast extraction of electrons or holes across the interface. We use TCSPC spectroscopy to quantitatively estimate the dynamics of the charge carriers ( Figure 3 e). Long lifetime of charge carriers (τ 10 =390ns) indicates the high electronic quality of the pristine perovskite film. (τ 10 is the time it takes for the initial PL intensity to decrease by 10 times). Consistent with the steady-state PL, in the presence of TiO 2 (τ 10 =49ns) as the electron extraction layer and spiro-OMeTAD (τ 10 =22ns) or CuSCN(τ 10 =16ns) in the perovskite film as a hole extraction layer. In contrast, hole injection from the valence band of perovskite to the highest occupied molecular orbital (HOMO) of HTM is much faster than that from the conduction band of perovskite to TiO. 2 The electron injection into the conduction band of CuSCN is faster. In addition, TCSPC shows that hole transfer across the perovskite-CuSCN junction is faster than that of the perovskite-spiro-OMeTAD interface, although the thermodynamic driving force (difference between the two energy levels) is lower at the perovskite-CuSCN interface. This difference can be explained by considering that the interfacial interaction between the Pb ions of the perovskite and the sulfide of CuSCN is stronger than that with the organic layer.
[0156] In addition to injection, charge transport through the HTM layers is another key process that critically affects the overall device performance. In fully assembled solar cells, 1.4 x 10 -6 cm 2. v -1 . s -1 and 1.2x 10 -3 cm 2 . v -1 . s -1 With similar charge separation and recombination dynamics in perovskites, the ~1000-fold higher hole mobility and thinner CuSCN layers present a clear advantage over spiro-OMeTAD, making the HTM of CuSCN layers efficient in its pristine form in contrast to spiro-OMeTAD, which requires high concentrations of p-dopants and other additives, such as organic lithium salts and 4-tert-butylpyridine, to reach its peak performance.
[0157] After successfully depositing a thin and conformal β-CuSCN layer, we investigated the photovoltaic (PV) properties of the device. From the current-voltage (JV) curves of the spiro-OMeTAD-based device ( Figure 4 a) The extracted PV parameters produced 23.35mA . cm -2 The short circuit current J SC , 1137mV open circuit voltage V OC and a fill factor FF of 77.5%, which results in an overall efficiency of 20.8%. The device with CuSCN as HTM produces 23.40 mA . cm -2 J SC , 1103mV V OC and 77.2% FF, which resulted in a PCE of 20.3% ( Figure 4 b). As is evident from the hysteresis index values, by comparing the forward and backward JV scans, the hysteresis effect is discernible for spiro-OMeTAD but is negligible for CuSCN ( Figure 4 c). Figure 4 c shows that the V generated by the CuSCN-based device is lower than that of the spiro-OMeTAD-based device. OC Slightly lower. To understand the V OC To account for this deficiency, we estimated the ideality factor (n), which is an indicator of the dominant recombination mechanism occurring within the working device. By using the equation: Fitting V OC The intensity correlation of the curve ( Figure 4 a. Figure 4b; inset), n of 1.46 and 1.51 were estimated for the spiro-OMeTAD-based device and the CuSCN-based device, respectively, indicating that V OC The difference in Jsc is due to the slightly higher single-molecule recombination occurring within the CuSCN-based device. Jsc as a function of irradiation shows a linear dependence ( Fig.10 ).
[0158] Table 1 takes 10mV . s -1 JV curves from the best performing spiro-OMeTAD-based device and CuSCN-based device measured in the backward and forward scans at a scan rate of Figure 4 a and Figure 4 b) Photovoltaic parameters in.
[0159]
[0160] Figure 4 c summarizes the statistical analysis of the PV parameters extracted from the J-V curves of 20 independent devices. The high PCE is reproducible not only for spiro-OMeTAD-based PSCs but also for CuSCN-based PSCs, as we observed an average J of 2.1 for CuSCN-based devices. SC =22.77±0.49mA . cm -2 , V OC =1090±11 mV and FF=0.74±0.02, which resulted in an average PCE of 19.34±0.75%. Similarly, for the spiro-OMeTAD-based devices, an average PCE of 19.6±0.77% was recorded, with an average J SC =22.6±0.55mA . cm -2 , V OC =1115±15 mV, and FF=0.75±0.02. In addition, to determine the stabilized (scan rate independent) PCE, the solar cell was probed at its maximum power point under full-sun illumination ( Figure 4 d). For the spiro-OMeTAD-based device and the CuSCN-based device, we recorded stabilized output powers corresponding to PCEs of 20.5% and 20.3%, respectively, which are in good agreement with the JV measurements. The integrated photocurrent densities obtained from the external quantum efficiency (EQE) spectra of the spiro-OMeTAD-based device and the CuSCN-based device are in good agreement with those obtained from the JV curves ( Figure 4e), which indicates that any spectral mismatch between our simulator and the AM-1.5 standard solar radiation is negligible.
[0161] Long-term stability and introduction of spacer layers into perovskite-based devices
[0162] The demonstration of long-term operational stability is a key requirement for the future development of PSC-based technologies. Under full sunlight illumination at the maximum power point, the CuSCN device showed very poor photostability, losing more than 50% of its initial efficiency ( Figure 4 f). In the literature, such instabilities of PSCs have been associated with degradation of the CuSCN / perovskite interface, however, using ALD to deposit ~2 nm Al between the perovskite and CuSCN layers 2 O 3 The layer shows no significant effect on initial degradation ( Figure 6 In an unprecedented move, we introduced a thin rGO spacer layer between the CuSCN layer and the gold layer ( Figure 5 ), which surprisingly leads to excellent operational stability under full-day illumination at 60 °C, as the resulting PSCs retain more than 95% of their initial efficiency after aging for 400 h, which significantly exceeds the stability recorded for spiro-OMeTAD devices under similar conditions ( Figure 7 Additional insight into the degradation was gained through X-ray photoelectron spectroscopy, which determined the oxidation of gold when the CuSCN devices were subjected to light soak testing ( Figure 8 ). Therefore, we believe that the instability of PSCs is not related to the degradation of the CuSCN / perovskite interface as commonly believed, but mainly originates from the CuSCN / Au contact. In addition, it has become imperative to demonstrate long-term thermal stability at high temperatures, mainly because the diffusion of metals through the spiro-OMeTAD layer at higher temperatures leads to degradation of the device. We examined the thermal stability of CuSCN-based devices coated with a thin layer of polymer at 85°C under ambient conditions in the dark. After 1000h, the CuSCN-based devices retained >85% of their initial efficiency ( Fig. 9). As is evident from the morphological analysis, the formation of a uniform CuSCN film hinders metal diffusion. Importantly, the CuSCN film does not require any additives to function as an efficient HTM, in contrast to PTAA and spiro-OMeTAD, which can only reach their peak performance in the presence of LiTFSI and 4-tert-butylpyridine, and in the case of the latter, also in the presence of a cobalt(III) complex acting as a p-dopant. These additives easily cross into the photoactive PSC layer and adversely affect the PV performance ( Fig. 9 ). Comparative analysis of stability tests showed that the severe degradation observed under operating conditions was light-driven and that this effect warrants further investigation.
[0163] Record performances demonstrated by operationally stable PSCs employing an all-inorganic charge extraction layer were achieved following the introduction of a simple dynamic method for depositing a thin and conformal CuSCN layer onto a perovskite layer. Importantly, we found that excellent operational stability at the maximum power point under full sunlight illumination could be achieved by introducing a thin rGO spacer layer between the CuSCN layer and the gold layer. 2 Such record PCEs shown by PSCs based on CuSCN (CuSnO and CuSCN), together with remarkable operational and thermal stability under long-term thermal stress, will facilitate their large-scale deployment.
[0164] in conclusion
[0165] The prominence of organic-inorganic perovskite solar cells (PSCs) can be attributed to the unprecedented progress in power conversion efficiency (PCE), which is mainly achieved by tuning the formation and composition of the absorber layer. 2 Layers have been developed and PCEs of >20% have been achieved by using spiro-OMeTAD [2,2',7,7'-tetrakis(N,N-di-p-methoxyphenyl-amine)9,9'-spirobifluorene] or polymer-based PTTA (polytriarylamine) as hole transport materials (HTMs). However, the cost of these HTMs is prohibitively high for large-scale applications, and long-term operational and thermal instabilities appear to be related to the prototype organic HTMs or their components. One strategy to address the cost and instability issues could be to use inexpensive inorganic hole extraction layers, similar to the use of TiO 2 However, when subjected to light soaking under practical operating conditions, i.e., at maximum power point and elevated temperature, inorganic HTMs such as NiO, CuI, Cs 2 Sn 6It remains a challenge to obtain a stable PCE > 20% by using CuSCN and TiO 2 As hole and electron extraction layers, respectively, the PSC obtains a stabilized PCE of 20.3%. We introduce a new method for solution deposition of dense (60 nm thickness) and highly conformal CuSCN layers, which provide fast carrier extraction and collection even in the absence of any dopants or additives. We show here that the notorious instability of PSCs using CuSCN as hole conductors is not related to the CuSCN / perovskite interface, but rather originates from the contact of CuSCN / Au. The introduction of a thin reduced graphene oxide (rGO) spacer layer between the CuSCN layer and the gold layer leads to the realization of robust operational stability, as the PSC retains more than 95% of its initial efficiency after aging for 400 h under full sunlight at 60 ° C. In addition, the CuSCN-based PSC shows excellent thermal stability under long-term thermal stress, retaining more than 85% of its initial efficiency after aging for 1000 h at 85 ° C. Importantly, CuSCN-based devices surpassed the stability of spiro-OMeTAD-based PSCs under both continuous irradiation and thermal stress.
[0166] Although the present invention has been explained in conjunction with the preferred embodiments thereof, it should be understood that many other possible modifications and variations may be made without departing from the scope of the invention as hereinafter claimed.
[0167] This application also involves the following:
[0168] 1) An optoelectronic device and / or photovoltaic device or photoelectrochemical device, comprising a conductive support layer, an n-type semiconductor, a sensitizer layer or a light absorber layer, a hole transport layer, a spacer layer and a back contact, wherein the n-type semiconductor is in contact with the sensitizer layer or the light absorber layer, the sensitizer layer or the light absorber layer comprises a perovskite or a metal halide perovskite material, the hole transport layer is in direct contact with the sensitizer layer or the light absorber layer and comprises an inorganic hole transport material or an inorganic p-type semiconductor, and the spacer layer is between the hole transport layer and the back contact and comprises a material different from the inorganic hole transport material and the material of the back contact.
[0169] 2) The optoelectronic device and / or photovoltaic device or photoelectrochemical device as described in 1), wherein the spacer layer comprises a material selected from the group consisting of reduced graphene oxide, graphene oxide, graphene, Ni, Co, Cr, Al 2 O 3 , Cu, C (carbon), ZrO 2 、SiO 2 、SiC、Si3 N 4 , Ca 3 (PO 4 ) 2 , an insulating polymer selected from polymethyl methacrylate (PMMA), a polycarbonate polymer, and boron nitride (BN).
[0170] 3) An optoelectronic device and / or a photovoltaic device or a photoelectrochemical device according to any one of the preceding items, wherein the n-type semiconductor comprises a metal oxide layer.
[0171] 4) An optoelectronic device and / or photovoltaic device or photoelectrochemical device according to any one of the preceding items, wherein the n-type semiconductor includes a metal oxide layer which is a dense layer, a mesoporous metal oxide layer is arranged on the dense layer, and the mesoporous metal oxide layer is a support structure for the perovskite or metal halide perovskite material.
[0172] 5) An optoelectronic device and / or photovoltaic device or photoelectrochemical device according to any one of the preceding items, wherein the n-type semiconductor comprises a semiconductor selected from Si, TiO 2 SnO 2 、ZnO、Zn 2 SnO 4 , Nb 2 O 5 , WO 3 、BaTiO 3 or SrTiO 3 Or any combination thereof.
[0173] 6) An optoelectronic device and / or photovoltaic device or photoelectrochemical device according to any one of the preceding items, wherein the hole transport layer comprises one or more inorganic hole transport materials or inorganic p-type semiconductors selected from NiO, CuO, CuSCN, CuI, CuGaO 2 、CuCrO 2 、CuAlO 2 、CsSnI 3 、MoO 3 or WO 3 or any combination thereof.
[0174] 7) An optoelectronic and / or photovoltaic device or a photoelectrochemical device according to any one of the preceding items, wherein the hole transport layer comprises a film that is free of pinholes and has a thickness of from 40 nm to 70 nm.
[0175] 8) An optoelectronic device and / or photovoltaic device or photoelectrochemical device according to any one of the preceding items, wherein the conductive support layer comprises a conductive material selected from the group consisting of an indium tin oxide (ITO) film substrate, a fluorine-doped tin oxide (FTO) film substrate, a ZnO-Ga 2 O 3 Film substrate, ZnO-Al 2 O 3 Film substrates, tin-based oxide film substrates, antimony-doped tin oxide (ATO), SrGeO 3 or zinc oxide.
[0176] 9) An optoelectronic device and / or photovoltaic device or photoelectrochemical device according to any of the preceding items, wherein the back contact comprises a material selected from a metal, porous carbon or a conductive polymer or a combination thereof, and the metal is selected from Pt, Au, Ni, Cu, Ag, In, Ru, Pd, Rh, Ir, or Os.
[0177] 10) An optoelectronic device and / or photovoltaic device or photoelectrochemical device according to any of the preceding items, wherein the perovskite or metal halide perovskite material is selected from a perovskite structure according to any one of the following formulas (I), (Ia), (Ib), (Ic), (Id), (Ie), (If) and / or (Ig):
[0178] AA'MX 4 (I)
[0179] AMX 3 (Ia)
[0180] AA'N 2 / 3 X 4 (Ib)
[0181] AN 2 / 3 X 3 (Ic)
[0182] BN 2 / 3 X 4 (Id)
[0183] BMX 4 (Ie)
[0184] (A l ) m AA'MX 3 (If)
[0185] (A l ) m AMX 3 (Ig)
[0186] in,
[0187] - A and A' are organic monovalent cations, the organic monovalent cations are independently selected from organic primary ammonium compounds, organic secondary ammonium compounds, organic tertiary ammonium compounds or organic quaternary ammonium compounds, including N-containing heterocyclic rings and ring systems, A and A' independently have from 1 to 60 carbons and 1 to 20 heteroatoms;
[0188] -A l Is selected from Cs + , Rb + , K + An inorganic cation, and m is an integer from 1 to 3, if m>1, then each A l different;
[0189] - B is an organic divalent cation selected from an organic primary ammonium compound, an organic secondary ammonium compound, an organic tertiary ammonium compound or an organic quaternary ammonium compound having from 1 to 60 carbon atoms and 2-20 heteroatoms and having two positively charged nitrogen atoms;
[0190] -M is selected from Cu 2+ 、Ni 2+ 、Co 2+ , Fe 2+ , Mn 2+ Cr 2+ , Pd 2+ 、Cd 2+ ,Ge 2+ Sn 2+ , Pb 2+ 、Eu 2+ , Yb 2+ 、[Sn i Pb (1-i) ] + 、[Sn j Ge (1-j) ] + and [Pb k Ge (1-k) ] + , i, j, and k are numbers between 0.0 and 1.0;
[0191] -N is selected from Bi 3+ and Sb 3+ groups; and,
[0192] -X is independently selected from Cl - Br - ,I - 、NCS - , CN - 、NCO - ; Selected from [I (3-m) Cl m] - , [I (3-n) Br n ] - , [Br (3-u) Cl u ] - , m, n, u are numbers between 0.0 and 3.0; and selected from C1 - Br - ,I - A combination of two anions.
[0193] 11) An optoelectronic and / or photovoltaic or photoelectrochemical device according to any of the preceding items, wherein the device is selected from an organic solar cell, a solid-state solar cell, a pn heterojunction, a phototransistor or an OLED (organic light emitting diode).
[0194] 12) A method for manufacturing an optoelectronic device and / or a photovoltaic device or a photoelectrochemical device, comprising:
[0195] - providing a conductive support layer;
[0196] - disposing an n-type semiconductor on the conductive support layer;
[0197] - disposing a sensitizer layer or a light absorber layer comprising a perovskite or metal halide perovskite material on the n-type semiconductor;
[0198] - placing a hole transport layer on the sensitizer layer or light absorber layer and subsequently applying a spacer layer;
[0199] - placing a counter electrode or a back contact electrode on the spacer layer;
[0200] wherein the hole transport layer comprises an inorganic hole transport material or an inorganic p-type semiconductor, and is deposited onto the sensitizer layer or the light absorber layer by a dynamic deposition method, the dynamic deposition method comprising depositing the inorganic hole transport material or the inorganic p-type semiconductor in a solution onto the sensitizer layer or the light absorber layer by a method selected from drop casting, doctor blade coating, electrodeposition, spin coating or spray coating while rotating the conductive support layer that supports the n-type semiconductor and the sensitizer layer or the light absorber layer; and
[0201] - the spacer layer comprises a material different from the material of the inorganic hole transport material and the counter electrode or back contact electrode.
[0202] 13) A method for manufacturing an optoelectronic device and / or a photovoltaic device or a photoelectrochemical device according to 12), wherein applying the inorganic hole transport material or inorganic p-type semiconductor in a solution to the sensitizer layer or the light absorber layer is provided by spin coating while rotating the conductive support layer.
[0203] 14) The method for manufacturing an optoelectronic device and / or a photovoltaic device or a photoelectrochemical device according to any one of 12) to 13), wherein the rotation of the conductive support layer is performed at a rotation speed of from 4000 rpm to 6000 rpm.
[0204] 15) A method for manufacturing an optoelectronic device and / or a photovoltaic device or a photoelectrochemical device according to any one of 12) to 14), wherein the spacer layer comprises a material selected from the group consisting of reduced graphene oxide, graphene oxide, graphene, Ni, Co, Cr, Al 2 O 3 , Cu, C (carbon), ZrO 2 、SiO 2 、SiC、Si 3 N 4 , Ca 3 (PO 4 ) 2 , an insulating polymer selected from polymethyl methacrylate (PMMA), a polycarbonate polymer, and boron nitride (BN).
Claims
1. An optoelectronic device or a photovoltaic device or a photoelectrochemical device, comprising a conductive support layer, an n-type semiconductor, a sensitizer layer or a light absorber layer, a hole transport layer, a spacer layer and a back contact, wherein the n-type semiconductor is in contact with the sensitizer layer or the light absorber layer, the sensitizer layer or the light absorber layer comprises a perovskite or a metal halide perovskite material, the hole transport layer is in direct contact with the sensitizer layer or the light absorber layer, and the spacer layer is between the hole transport layer and the back contact, wherein - the hole transport layer does not contain p-dopants or organic hole transport materials and comprises an inorganic hole transport material or an inorganic p-type semiconductor, which in its original form is selected from NiO, CuO, CuSCN, CuI, CuGaO 2 、CuCrO 2 、CuAlO 2 、CsSnI 3 、MoO 3 or WO 3 or any combination thereof, - the spacer layer comprises a material different from the inorganic hole transport material and the material of the back contact, and the spacer layer is selected from: reduced graphene oxide, Cr and Al 2 O 3 ,and - The spacer layer prevents a reaction between the inorganic hole transport material or inorganic p-type semiconductor and the back contact under stress or under irradiation. 2 . The optoelectronic device or photovoltaic device or photoelectrochemical device according to claim 1 , wherein the n-type semiconductor comprises a metal oxide layer.
3. An optoelectronic device or a photovoltaic device or a photoelectrochemical device according to claim 2, wherein the n-type semiconductor comprises a metal oxide layer which is a dense layer, a mesoporous metal oxide layer is arranged on the dense layer, and the mesoporous metal oxide layer is a support structure for the perovskite or metal halide perovskite material.
4. The optoelectronic device, photovoltaic device or photoelectrochemical device according to claim 2, wherein the n-type semiconductor comprises a semiconductor selected from Si, TiO 2 SnO 2 、ZnO、Zn 2 SnO 4 , Nb 2 O 5 , WO 3 、BaTiO 3 or SrTiO 3 Or any combination thereof.
5. The optoelectronic device or photovoltaic device or photoelectrochemical device of claim 1, wherein the hole transport layer comprises a film free of pinholes and having a thickness of from 40 nm to 70 nm.
6. The optoelectronic device or photovoltaic device or photoelectrochemical device according to claim 1, wherein the conductive support layer comprises a conductive material selected from tin-based oxide film substrates.
7. The optoelectronic device or photovoltaic device or photoelectrochemical device according to claim 1, wherein the conductive support layer comprises a conductive material selected from the group consisting of an indium tin oxide (ITO) film substrate, a fluorine-doped tin oxide (FTO) film substrate, a ZnO-Ga 2 O 3 Film substrate, ZnO-Al 2 O 3 Film substrate, antimony-doped tin oxide ATO, SrGeO 3 or zinc oxide.
8. An optoelectronic device or a photovoltaic device or a photoelectrochemical device according to claim 1, wherein the back contact comprises a material selected from a metal, a porous carbon or a conductive polymer or a combination thereof, and the metal is selected from Pt, Au, Ni, Cu, Ag, In, Ru, Pd, Rh, Ir, or Os.
9. The optoelectronic device or photovoltaic device or photoelectrochemical device according to claim 1, wherein the perovskite or metal halide perovskite material is selected from a perovskite structure according to any one of the following formula (I), formula (Ia), formula (Ib), formula (Ic), formula (Id), formula (Ie), formula (If) and / or formula (Ig): AA'MX 4 (I) AMX 3 (Ia) AA'N 2 / 3 X 4 (One) AN 2 / 3 X 3 (Ic) BN 2 / 3 X 4 (Id) BMX 4 (Ie) (A l ) m AA'MX 3 (If) (A l ) m AMX 3 (Ig) in, - A and A' are organic monovalent cations, the organic monovalent cations are independently selected from organic primary ammonium compounds, organic secondary ammonium compounds, organic tertiary ammonium compounds or organic quaternary ammonium compounds, including a N-containing ring system, A and A' independently have from 1 to 60 carbons and 1 to 20 heteroatoms; - A l Is selected from Cs + , Rb + , K + An inorganic cation, and m is an integer from 1 to 3, if m>1, then each A l different; - B is an organic divalent cation selected from an organic primary ammonium compound, an organic secondary ammonium compound, an organic tertiary ammonium compound or an organic quaternary ammonium compound having from 1 to 60 carbon atoms and 2 to 20 heteroatoms and having two positively charged nitrogen atoms; - M is selected from Cu 2+ 、Ni 2+ 、Co 2+ , Fe 2+ , Mn 2+ Cr 2+ , Pd 2+ 、Cd 2+ ,Ge 2+ Sn 2+ , Pb 2+ 、Eu 2+ , Yb 2+ 、[Sn i Pb (1-i) ] + 、[Sn j Ge (1-j) ] + and [Pb k Ge (1-k) ] + , i, j, and k are numbers between 0.0 and 1.0; - N is selected from Bi 3+ and Sb 3+ groups; and, - X is independently selected from Cl - Br - ,I - 、NCS - , CN - 、NCO - ; Selected from [I (3-m) Cl m ] - , [I (3-n) Br n ] - , [Br (3-u) Cl u ] - , m, n, u are numbers between 0.0 and 3.0; and selected from C1 - Br - ,I - A combination of two anions.
10. The optoelectronic device or photovoltaic device or photoelectrochemical device according to claim 1, wherein the device is selected from an organic solar cell, a solid-state solar cell, a pn heterojunction, a phototransistor or an organic light emitting diode (OLED).
11. A method for manufacturing an optoelectronic device, a photovoltaic device or a photoelectrochemical device, comprising the following consecutive steps: - providing a conductive support layer; - disposing an n-type semiconductor on the conductive support layer; - disposing a sensitizer layer or a light absorber layer comprising a perovskite or metal halide perovskite material on the n-type semiconductor; - placing a hole transport layer on the sensitizer layer or light absorber layer and subsequently applying a spacer layer on the hole transport layer; - placing a counter electrode or a back contact electrode on the spacer layer; wherein the hole transport layer comprises an inorganic hole transport material or an inorganic p-type semiconductor, and is deposited onto the sensitizer layer or the light absorber layer by a dynamic deposition method, wherein the dynamic deposition method comprises depositing the inorganic hole transport material or the inorganic p-type semiconductor in a solution onto the sensitizer layer or the light absorber layer by a method selected from drop casting, blade coating, electrodeposition, spin coating or spray coating while rotating the conductive support layer that supports the n-type semiconductor and the sensitizer layer or the light absorber layer; - the spacer layer comprises a material different from the inorganic hole transport material and the back contact material, and the spacer layer is selected from: reduced graphene oxide, Cr and Al 2 O 3 ,and - The spacer layer prevents a reaction between the inorganic hole transport material or inorganic p-type semiconductor and the back contact material under stress or under irradiation.
12. A method for manufacturing an optoelectronic device, a photovoltaic device or a photoelectrochemical device according to claim 11, wherein applying the inorganic hole transport material or inorganic p-type semiconductor in a solution to the sensitizer layer or light absorber layer is provided by spin coating while rotating the conductive support layer.
13. The method for manufacturing an optoelectronic device or a photovoltaic device or a photoelectrochemical device according to any one of claims 11 to 12, wherein the rotation of the conductive support layer is performed at a rotation speed of from 4000 rpm to 6000 rpm.
